2011
DOI: 10.1152/ajpendo.00114.2011
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exercise training early in life restores deficits in pancreatic β-cell mass associated with growth restriction in adult male rats

Abstract: Fetal growth restriction is associated with reduced pancreatic β-cell mass, contributing to impaired glucose tolerance and diabetes. Exercise training increases β-cell mass in animals with diabetes and has long-lasting metabolic benefits in rodents and humans. We studied the effect of exercise training on islet and β-cell morphology and plasma insulin and glucose, following an intraperitoneal glucose tolerance test (IPGTT) in juvenile and adult male Wistar-Kyoto rats born small. Bilateral uterine vessel ligati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(138 citation statements)
references
References 53 publications
6
129
1
2
Order By: Relevance
“…31 Studies indicated which exercise training promoted β-cell growth dramatically and growth restricted animals had partial β-cell mass restoration (by 60-68%) if they were regularly exercising. 32 Kiraly et al (2007) demonstrated that swimming exercise in type 2 diabetic rats elevates β-cell mass by increasing the number of β-cells per. 19 In the present study, β-cell apoptosis through measuring of p53 levels in pancreas tissue of type 2 diabetic rats were decreased by voluntary running.…”
Section: Discussionmentioning
confidence: 99%
“…31 Studies indicated which exercise training promoted β-cell growth dramatically and growth restricted animals had partial β-cell mass restoration (by 60-68%) if they were regularly exercising. 32 Kiraly et al (2007) demonstrated that swimming exercise in type 2 diabetic rats elevates β-cell mass by increasing the number of β-cells per. 19 In the present study, β-cell apoptosis through measuring of p53 levels in pancreas tissue of type 2 diabetic rats were decreased by voluntary running.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma glucose concentrations were measured in duplicate using a scaled-down version of the enzymatic fluorometric analysis (Laker et al 2011, Gallo et al 2012b. Plasma insulin concentrations were measured in duplicate using a commercially available rat insulin RIA kit (Millipore, Abacus ALS, Brisbane, QLD, Australia; Siebel et al 2008, Wadley et al 2008, Laker et al 2011, Gallo et al 2012b.…”
Section: Plasma Metabolite Analysesmentioning
confidence: 99%
“…Plasma insulin concentrations were measured in duplicate using a commercially available rat insulin RIA kit (Millipore, Abacus ALS, Brisbane, QLD, Australia; Siebel et al 2008, Wadley et al 2008, Laker et al 2011, Gallo et al 2012b. Plasma triglyceride concentrations were measured in duplicate on an automated centrifugal analyzer (Cobas Integra 400, Roche Diagnostics).…”
Section: Plasma Metabolite Analysesmentioning
confidence: 99%
See 2 more Smart Citations